Evacuation Safety Evaluation in the Event of a Fire in a Shopping Center with a Connected Passageway in Korea - et. al., Seo-Young Kim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this study, scenarios were developed to evaluate evacuation safety in the event of a fire in a shopping center with a connected passageway and to reduce Required Safe Egress Time (RSET). The RSET for all occupants by scenario is as follows: The first scenario which used the general evacuation route took 20 minutes and 7 seconds. The second scenario which used the third floor’s connected passageway for third and fourth floor, and using first floor entrance for first and second floor to evacuate took 14 minutes and 11 seconds. The evacuation time was 36 minutes and 52 seconds for scenario 3, which only used the fire escape stairs. The fourth scenario took 4 minutes and 19 seconds and used a connected passageway on every floor. Overall, this study shows that RSET for all occupants is reduced when a connected passageway is installed on every floor in shopping centers. Henceforth, more research is needed to determine whether connected passageway is a single firefighting object or a separate structure.